DETAILED HEAT TRANSFER MEASUREMENTS NEAR AND WITHIN THE ENTRANCE OF A FILM COOLING HOLE. - Byerley, A; Ireland, P; Jones, T; Ashton, SA (1988)
An experimental investigation was conducted to obtain highly detailed convective heat transfer measurements on an internal cooling duct wall around the entrance to a film cooling hole. Measurements were also made within the first five diameters of the film cooling hole. Thermochromic liquid crystals were used as surface temperature indicators in a large scale, perspex tunnel during the transient tests. The results are presented as contours of heat transfer coefficient normalized by that for the plain duct wall. Significant enhancement on the duct wall was measured up to a distance of seven hole diameters downstream of the hole. Both the magnitude and the shape of the enhancement contours were found to be highly dependent on the hole-to-duct velocity ratio.